Atomic layer etching of SiO2 with Ar and CHF 3 plasmas: A self‐limiting process for aspect ratio independent etching. Issue 9 (22nd May 2019) - Dallorto, Stefano; Goodyear, Andy; Cooke, Mike; Szornel, Julia E.; Ward, Craig; Kastl, Christoph; Schwartzberg, Adam; Rangelow, Ivo W.; Cabrini, Stefano
Abstract: With ever increasing demands on device patterning to achieve smaller critical dimensions, the need for precise, controllable atomic layer etching (ALE) is steadily increasing. In this work, a cyclical fluorocarbon/argon plasma is successfully used for patterning silicon oxide by ALE in a conventional inductively coupled plasma tool. The impact of plasma parameters and substrate electrode temperature on the etch performance is established. We achieve the self‐limiting behavior of the etch process by modulating the substrate temperature. We find that at an electrode temperature of −10°C, etching stops after complete removal of the modified surface layer as the residual fluorine from the reactor chamber is minimized. Lastly, we demonstrate the ability to achieve independent etching, which establishes the potential of the developed cyclic ALE process for small scale device patterning. Abstract : Advanced nanomanufacturing requires the ability to achieve atomic scale etching control and material selectivity during pattern transfer. Cyclical fluorocarbon/argon‐based atomic layer etching satisfied these needs and is here investigated on flat and patterned silicon oxide substrates. Self‐limiting behavior is reached by modulating plasma parameters and electrode temperature. Aspect ratio independent etching is demonstrated during the pattern transfer of features.